The Tantangan Generasi Z dalam Menyeimbangkan Gaya Hidup Sustainable Fashion dan Tren Fomo - Rahmadania, Salu; Setiawan, Joe Harrianto; Putri, Novaldha Andhianthie (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2025)
Environmental awareness, Fear of Missing Out (FOMO), and cognitive dissonance interact to shape Gen Z’s consumer behavior. The rapid influence of social media intensifies FOMO, creating a psychological conflict between sustainability values and consumption practices. Using cognitive dissonance theory (Festinger, 1957), this study explores how Gen Z rationalizes their consumption to align with social expectations. A qualitative approach with in-depth interviews analyzes variations in environmental awareness and consumption decisions. Findings reveal that social pressure and media influence significantly drive impulsive consumption. While some individuals adopt sustainable lifestyles, many struggle to overcome consumption patterns reinforced by social validation. The conflict between sustainability awareness and consumer habits highlights the complexity of balancing ethical considerations with social identity.